A comparison of hedonic and emotional responses to common odors delivered by qPODs (Portable Olfactive Devices) and traditional sniff jars. (March 2020) - Gaby, Jessica M.; Tepper, Beverly J.
Highlights: Mood following odor presentation was similar when odors were presented in jars and qPODs. Odors were rated as more intense (but not more pleasant) in qPODs than jars. Mood signatures were consistent for each odorant regardless of presentation type. Abstract: qPODs (Portable Olfactive Devices, Curion) are novel olfactory delivery systems which allow for sampling of a wide variety of stimulus types. Participants evaluate odors by opening a port at the top of the qPOD and sampling a controlled air stream. Though they are often used in marketing studies, their potential use in empirical research has yet to be investigated. We asked participants to smell citral, citronellol, geraniol, PEA, nonalactone, and vanillin delivered via qPODs and by traditional sniff jars, and compared both hedonic and emotional responses. Across four sessions, 31 participants evaluated the pleasantness and intensity of each odor in qPODs and sniff jars. Their emotional reactions to the odors were captured with the PANAS (Positive And Negative Affect Schedule) at the beginning of each testing session, and then again after exposure to each odor. They also completed the newly developed Mood Signature Questionnaire, which asks participants to assign a mood to each odor, rather than reporting how it makes them feel. Though odors presented in the sniff jars were rated significantly more intense (p < 0.001), there were no differences between presentation types for perceived pleasantness, changes in positive or negative mood following odor exposure, or which emotional descriptors (Mood Signatures) participants assigned to the odors. Our results suggest that responses to odor stimuli presented using qPODs are comparable to traditional sniff jars, thus establishing the qPOD as a potential new tool for studies employing a range of olfactory stimuli.